Legal Challenges of Creditor Protection against Unfair Terms in a Personal Loan Consumer Protection Unfairness in a Personal Loan Contract in Iraq - Marwah Saadi Saleh, Asmah Laili Yeon (International Journal of Advanced Science and Technology, 2020)
Nowadays, consumers are the driver of the banking marketplace.  Their protection of dealing with banks should be the priority target because a personal loan contract is considered as a standard agreement contract between the bank and consumer.  It takes effect when the bank lends the money as a condition for the validity of the contract. However, it is concurred that a personal loan is risky because it involves a standard form contract provided by the bank. The bank is the stronger party in a credit contract agreement prepared by the professional staff and financial experts. In Iraq, there are loopholes in the law for consumer protection who contracts with the bank. The consumer party in the standard form personal loan contract has suffered from unfair terms in high-interest-rate condition. Besides that, banks may alter conditions without notifying borrowers.  Also, neither legal policy nor a single piece of law is available that can deal with the unfairness in a personal loan contract.  In uncovering such prominent issues, this research aims to poll on via practical ways by first investigating the legal challenges arising from the creditor protection against unfair terms included in loan contracts, and second by analysing the Iraqi laws and its adequacy in protecting creditors from unfair contract terms in bank loan contracts. With those challenges, this paper attempts to use a legal research method to analyse the related provisions of the Iraqi Civil Code (ICC) 1951 and Consumer Protection Law (CPL) 2010 which deal with consumer protection. An unstructured interview method was used to obtain information from the legal experts involved in civil courts, civil law academicians, and banks administrators. This study finds that the personal loan contract is a specified contract subject to general rules in the ICC, which is out dated and does not fulfil the required protection. Albeit the civil court judges commonly used to apply it until now, yet these laws are considered as inadequate and not developed in a manner that protects consumers of the personal loan contract. The CPL is not active and has failed to cover the issues of unfair terms in a personal loan contract. The presence of a credible and effective regulatory regime could act as a source of confidence and comfort in the financial system. It is recommended that a special law be enacted to deal with the aforementioned cases and risks that surround creditors when they contract with banks. The provisions of the CPL can also be activated to assign a special board for the financial litigation against banks. The CPL needs an urgent amendment to keep up with the development of the laws in the United Kingdom in such challenges